IMPLEMENTASI KEBIJAKAN PELAYANAN DAN PENERBITAN SERTIFIKAT VAKSINASI INTERNASIONAL DI KANTOR KESEHATAN PELABUHAN (KKP) KELAS III TEMBILAHAN - Nike Nurfadilla; Hasim As’ari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Policy implementation of service and issuance of international vaccination certificates are policies issued by the Ministry of Health at the Directorate General disease prevention and control aimed at preventing and controlling the risk of spreading cross-border infectious diseases.As for the background of this research because Indonesian people, including those who actively visit Saudi Arabia to perform Hajj and Umrah pilgrimages and administer the International Vaccine Certificate. The purpose of this study is to determine the implementation of policies and services and the issuance of international vaccination certificates and the factors that hinder the implementation of these policies. This research uses purposive sampling technique with qualitative research type using descriptive approach and the required data both primary and secondary data are obtained by observation, interview and documentation techniques, for further analysis is carried out. This research uses Mentality, System,Networking(MSN)-Approuchteory from YuliantoKadji.The results of this study indicate that: first, the implementation of service policies and the issuance of international vaccination certificates at the Port Health Office (KKP) Class III Tembilahanhas not been optimal. Second, the inhibiting factors in implementing the policy are responsibility, outreach, KKP apparatus resources, and clinical legality. Key words: Implementation, Mentality, System, Networking (MSN)-Approach